Seroprevalence and characterization of Brucella species in cattle slaughtered at Gauteng abattoirs, South Africa - Kolo, Francis B. (Vet Med Sci, 2019)
BACKGROUND: Brucellosis is an infectious and contagious zoonotic bacterial disease of both humans and animals. In developing countries where brucellosis is endemic, baseline data on the prevalence of brucellosis, using abattoir facilities, is important. OBJECTIVES: The aim of this study was to determine the seroprevalence of antibodies against Brucella in slaughter cattle at Gauteng province, South Africa and to characterize isolates of Brucella spp. METHODS: In this cross‐sectional study, un‐clotted blood samples with corresponding organ tissue samples were collected from slaughtered cattle. Serological [Rose Bengal test (RBT), complement fixation test (CFT) and indirect ELISA (iELISA)], molecular (PCR) and bacteriological methods were used to detect Brucella antibodies and Brucella spp. from 200 slaughtered cattle in 14 abattoirs. RESULTS: The RBT revealed a seroprevalence of brucellosis as 11.0% (22 of 200) and iELISA confirmed 5.5% (11 of 200). The estimated seroprevalence from RBT and iELISA was 5.5% while RBT and CFT was 2.0% (4 of 200). Brucella melitensis (n = 6) and B. abortus (n = 5) were isolated from 11 cattle tissues (5.5%) as confirmed to species level with AMOS PCR and differentiated from vaccine strains with Bruce‐ladder PCR. Seven of the 11 isolates originated from seropositive cattle of which five were biotyped as B. abortus bv 1 (n = 2) and B. melitensis bv 2 (n = 1) and B. melitensis bv 3 (n = 2). CONCLUSIONS: This is the first documentation of B. melitensis in cattle in South Africa. The zoonotic risk of brucellosis posed by Brucella‐infected slaughter cattle to abattoir workers and consumers of improperly cooked beef cannot be ignored.